Not what it looks like: mate-searching behaviour, mate preferences and clutch production in wandering and territory-holding female fiddler crabs. Issue 8 (August 2016) - Peso, M.; Curran, E.; Backwell, P. R. Y.
Abstract : Risks inherent in mate-searching have led to the assumption that females moving sequentially through populations of courting males are sexually receptive, but this may not be true. We examined two types of fiddler crab females: wanderers moving through the population of courting males and residents that were occupying and defending their own territories. Sometimes residents leave territories to look for new burrows and we simulated this by displacing wanderers and residents and observing their behaviour while wandering. We predicted that the displaced wanderers would exhibit more mate-searching behaviours than resident females. However, wandering and resident females behaved nearly identically, displaying mate-searching behaviours and demonstrating matching mate preferences. Also, males behaved the same way towards both female types and similar proportions of wanderers and residents stayed in a male's burrow to mate. But more wanderers than residents produced egg clutches when choosing a burrow containing a male, suggesting females should be categorized as receptive and non-receptive. Visiting and rejecting several males is not the defining feature of female mate choice. Moving across the mudflat by approaching and leaving a succession of burrows (mostly occupied by males) is an adaptive anti-predator behaviour that is useful in the contexts of mate-searching and territory-searching.